2021
DOI: 10.1186/s13063-021-05369-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost talk: protocol for a stepped-wedge cluster randomized trial of an intervention helping patients and urologic surgeons discuss costs of care for slow-growing prostate cancer during shared decision-making

Abstract: Background Costs of care are important to patients making cancer treatment decisions, but clinicians often do not feel prepared to discuss treatment costs. We aim to (1) assess the impact of a conversation-based decision aid (Option Grid) containing cost information about slow-growing prostate cancer management options, combined with urologic surgeon training, on the frequency and quality of patient-urologic surgeon cost conversations, and (2) examine the impact of the decision aid and surgeon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…45 A randomized trial is ongoing to assess impact of "Cost Talk," a conversation decision aid for treatment decisions about cancer. 46 Others have explored the use of shared decisionmaking tools to trigger discussions about cost. 47 The interdisciplinary team can contribute to conversations about cost, including social workers and case managers 48 but, our study shows, cannot be limited to discussions of enrolling for supplemental security income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 A randomized trial is ongoing to assess impact of "Cost Talk," a conversation decision aid for treatment decisions about cancer. 46 Others have explored the use of shared decisionmaking tools to trigger discussions about cost. 47 The interdisciplinary team can contribute to conversations about cost, including social workers and case managers 48 but, our study shows, cannot be limited to discussions of enrolling for supplemental security income.…”
Section: Discussionmentioning
confidence: 99%
“…Natt et al have reported on the success of standardized patient scenarios to teach medical students to discuss cost as a part of medical decision-making (45). A randomized trial is ongoing to assess impact of "Cost Talk," a conversation decision aid for treatment decisions about cancer (46). Others have explored the use of shared decision-making tools to trigger discussions about cost (47).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Detailed methods are described in a published protocol 35 . Reporting follows the 2018 CONSORT extension for stepped wedge randomised controlled trials 36 …”
Section: Methodsmentioning
confidence: 99%
“…Step 1: identifying the problem This research question arose from an existing project, evaluating a prostate cancer treatment decision aid that includes relative cost information led by a member of the research team (Politi et al, 2021). Formative interviews identified a gap in cost information for those making decisions about prostate cancer treatment options and their clinicians.…”
Section: Methodsmentioning
confidence: 99%
“…Survival is similar for non-metastatic, localized prostate cancer across treatment options (i.e., radiation, surgery, active surveillance), but patients must weigh quality of life tradeoffs (e.g., distress, urinary incontinence, erectile dysfunction) during this preference-sensitive decision (Bill-Axelson et al, 2014;Lamers et al, 2017;Sanda et al, 2018). Providing cost estimates of the cost burden associated with different prostate cancer treatment pathways alongside clinical tradeoffs can support this decision; cost can be a substantial qualityof-life tradeoff that is often not discussed or not precisely known to patients during decision-making (Politi et al, 2021). There is a growing call regarding the importance of including direct and indirect cost information in shared-decision making conversations for prostate cancer as nonmetastatic treatment outcomes are generally similar and costs can help inform patients as they weigh their options (Ubel et al, 2013;Politi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%